The Brain Injury Screening Tool (BIST): Tool Development, Factor Structure and Validity - Theadom, A; Hardaker, N; Bray, C; Siegert, RJ; Henshall, K; Forch, K; Fernando, K; King, D; Fulcher, M; Jewell, S; Shaikh, N; Gottgtroy, RB; et al. (Public Library of Science (PLoS), 2021)
Currently health care pathways (the combination and order of services that a patient receives to manage their injury) following a mild traumatic brain injury vary considerably. Some clinicians lack confidence in injury recognition, management and knowing when to refer. A clinical expert group developed the Brain Injury Screening Tool (BIST) to provide guidance on health care pathways based on clinical indicators of poor recovery. The tool aims to facilitate access to specialist services (if required) to improve longer term prognosis. The tool was developed using a three-step process including: 1) domain mapping; 2) item development and 3) item testing and review. An online retrospective survey of 114 adults (>16 years) who had experienced a mild brain injury in the past 10 years was used to determine the initial psychometric properties of the 15-item symptom scale of the BIST. Participants were randomised to complete the BIST and one of two existing symptom scales; the Rivermead Post-concussion Symptom Questionnaire (RPQ) or the Sports Concussion Assessment Test (SCAT-5) symptom scale to determine concurrent validity. Participant responses to the BIST symptom scale items were used to determine scale reliability using Cronbach’s alpha. A principal components analysis explored the underlying factor structure. Spearman’s correlation coefficients determined concurrent validity with the RPQ and SCAT-5 symptom scales. The 15 items were found to require a reading age of 6–8 years old using readability statistics. High concurrent validity was shown against the RPQ (r = 0.91) and SCAT-5 (r = 0.90). The BIST total symptom scale (α = 0.94) and the three factors identified demonstrated excellent internal consistency: physical/emotional (α = 0.90), cognitive (α = 0.92) and vestibular-ocular (α = 0.80). This study provides evidence to support the utility, internal consistency, factor structure and concurrent validity of the BIST. Further research is warranted to determine the utility of the BIST scoring criteria and responsiveness to change in patients.